Digital transformation and sustainable firm performance in global manufacturing: A systematic review - Jiang, Chao; Pimdee, Paitoon; Sukkamart, Aukkapong (Edelweiss Applied Science and Technology, 2026)
Digital transformation is a driving force in sustainable industrial development, yet evidence on the sustainable manufacturing outcomes of digital business initiatives remains incomplete. This systematic literature review (SLR) analyzed 70 empirical studies published between 2010 and January 2026 that examined digital transformation processes resulting in economic, environmental, and innovation performance outcomes. The research combined various digital transformation processes through which organizations achieved business success, using five principal mediator pathways that follow the PRISMA 2020 guidelines. The study results showed that digital transformation does not directly enhance organizational performance; instead, it occurs through the development of organizational capabilities, the transformation of processes, the execution of innovation initiatives, and sustainability-focused activities. The research also shows that capability-based mechanisms are the most common pathways, followed by operational and innovation-mediated pathways. The research field shows a prevailing pattern of using cross-sectional survey methods, which create challenges for establishing causal relationships and evaluating enduring sustainability outcomes. The review shows that digital transformation needs to be better understood, as it plays a vital role in sustainable manufacturing transitions, according to established explanatory frameworks that link digital transformation to sustainable business results. The research study identifies three primary obstacles, which include conceptual fragmentation, measurement inconsistencies, and geographical concentration, while suggesting future research directions.